Relevansi Nilai Lokasamgraha Terhadap Wacana Politk Identitas Dan Masa Depan Kebangsaan - Puspo Renan Joyo; Mujiyono Mujiyono; Kadek Ayu Ariningsih (Jayapangus Press, 2022)
This article is a study of national identity, identity politics, and the value of Lokasamgraha in Hinduism and their relevance to the escalation of identity politics and the discourse of the future of the nation. This is a library research with qualitative approach. Lokasamgraha is a material object in this research. This research used data collection techniques and using data analysis, namely: interpretative, holistic and descriptive. Results of this study are: 1) national identity is Bhinneka Tunggal Ika inspired by Pancasila and Undang-Undang Dasar 1945, and explored into three, fundamental identity, instrumental identity, and natural identity; 2) identity politics is irrelevant and has lost its meaning. The emergence of identity politics lately must be viewed as a threat and sabotage against the existence of Indonesia. And the last is 3) the value of Lokasamgraha is at odds with identity politics but found similar resonance with the discourse on the future of the nation. Lokasamgraha finds its urgency in two things, namely: identity politics and the future of nation.